Head-to-head comparison of four cerebrospinal fluid and three plasma neurofilament light chain assays in Parkinsonism - Simone Baiardi; Marcello Rossi; Giulia Giannini; Angela Mammana; Barbara Polischi; Luisa Sambati; Andrea Mastrangelo; Franco Magliocchetti; Pietro Cortelli; Sabina Capellari; Giovanna Calandra Buonaura; Piero Parchi (npj Parkinson's Disease)
Abstract Neurofilament light chain protein (NfL) is a valuable biomarker for the differential diagnosis between Parkinson’s disease (PD) and atypical parkinsonian disorders (APD). Here, we compared the performance of four cerebrospinal fluid (CSF) and three plasma NfL immunoassays in 253 PD and 265 APD. We measured NfL by ELISA in CSF and by SiMoA, CLEIA, and ELLA in both CSF and plasma. Additionally, we assessed Lewy body pathology by CSF α-synuclein real-time quaking-induced conversion assay (α-syn-RT-QuIC). In each biofluid, the tested assays showed comparable precision; however, CSF NfL showed higher diagnostic accuracy than plasma NfL for discriminating PD from APD (AUC range 0.966–0.974 vs 0.917–0.924). Combining CSF NfL and α-syn-RT-QuIC increased diagnostic accuracy. These results confirm the high diagnostic value of NfL in patients with parkinsonism, even when different assays are used. Combining CSF NfL and α-syn-RT-QuIC provides the highest accuracy, followed by CSF NfL and plasma NfL.